Experience in the Treatment of Chronic Viral Hepatitis C in Children Born to HIV-positive Women - V. N. Timchenko; Yu. A. Arkhipova; O. V. Bulina (LLC "Diagnostics and Vaccines", 2015)
The article presents information obtained from the analysis of the stories of 40 children up to 4 years old left without parental care and infected with hepatitis C through vertical transmission. Authors analyzed the results of integrated treatment of the disease with inclusion of combined antiviral immunomodulatory drug VIFERON®. The efficacy of VIFERON® in chronic viral hepatitis C in infants is confirmed.